1999
DOI: 10.1590/s0066-782x1999000700005
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of subsequent pregnancy after peripartum cardiomyopathy

Abstract: OBJECTIVE: To assess the effect of subsequent pregnancy after peripartum cardiomyopathy (PPCM) on maternal and fetal outcome. METHODS: Prospective study of 34 patients with the diagnosis of PPCM (mean age= 26years). At the time of first diagnosis 5 were in NYHA functional class (FC) II for heart failure, one in FC III and 28 in FC IV. After clinical treatment, patients were advised to avoid new pregnancies and a follow-up was obtained. RESULTS: There were 12 (35.3%) subsequent pregnancies in patients (pt) aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Data on SSPs in women with a previously diagnosed PPCM are limited. Table summarizes the studies of women who had a SSP after being diagnosed with PPCM . However, the mode of data collection is highly variable with some studies not reporting the LVEF of the index pregnancy, nor the cardiac dimensions, left and right ventricular function at onset of the SSP.…”
Section: How Can Patients Be Best Advised About the Risks For A Subsementioning
confidence: 99%
“…Data on SSPs in women with a previously diagnosed PPCM are limited. Table summarizes the studies of women who had a SSP after being diagnosed with PPCM . However, the mode of data collection is highly variable with some studies not reporting the LVEF of the index pregnancy, nor the cardiac dimensions, left and right ventricular function at onset of the SSP.…”
Section: How Can Patients Be Best Advised About the Risks For A Subsementioning
confidence: 99%
“…All patients who died during or after the SSP entered the SSP with persistent LV dysfunction or persistent cardiomyopathy, according to seven studies. 14 16 17 21 22 24 25 However, a prospective cohort from Brazil reported there were no statistically significant differences between surviving and deceased women in terms of socioeconomic status, LV and right ventricular (RV) function before entering SSP. At the time of hospitalisation, congestive HF and lower LV and RV function were more frequently observed in women who died after pregnancy than in the group of surviving patients.…”
Section: Resultsmentioning
confidence: 99%
“… 10 14 16 18 20 21 A prospective cohort from Brazil reported increased heart size in 7 out of 12 patients in which 1 of them also developed pre-eclampsia. 14 Pre-eclampsia emerged as the predominant hypertensive complication in most studies, accounting for 50% of the total hypertension cases seen. 10 14 16 20 Codsi et al 16 and Goland et al 10 both found three cases of gestational diabetes mellitus as one of the aggravating factors of the pregnancy.…”
Section: Resultsmentioning
confidence: 99%